TANTANGAN INDEPENDENSI MEDIA DALAM PEMILU: KASUS KOMPAS.COM - Khotimah, Nurul (Islamic Communication Journal, 2019)
The aim of this study is to describe media ideology and construct media independence in the 2019 political year. Ideology has a major influence on the determination of media content. It is as if the general election democracy party cannot be separated from the mass media, so that the reporting of events "attacking each other" by the candidate pair cannot be avoided in the general election contestation. The object of the study was Kompas.com reporting on time limitations during the 2019 presidential and vice presidential election campaign. The research method used was qualitative library research. Data collection techniques using documentation. The results showed that the challenge of media ideology in maintaining the independence of media coverage in the political year must use the principles of independence. They are the presence or absence of opinion, personalization, sensation, stereotype, linkage, and accuracy in reporting.